Multi-cationic ionic liquid combination enabling 86-fold enhancement in frequency response and superior energy density in all-solid-state supercapacitors. (September 2022) - Jha, Mihir Kumar; Sunariwal, Neelam; Parker, Bradyn J.; Cameron, Neil; Subramaniam, Chandramouli
Abstract: Polymer ionic-conductor electrolytes with seamless electrode-electrolyte interface are indispensable for extracting the full potential of all-solid-state electrochemical double layer capacitors. While ionic liquids are among the best ionic conductors in liquid state and offer a wide potential window, translating their ionic mobility and activity to solid-state is important, yet challenging. In this direction, we report a mixed ionic liquid based solid electrolyte with an ionic conductivity of 1 mS/cm that delivers 86-fold higher scan-rate operability and 2.6 times lower relaxation time constant than their individual constituents. Specifically, a flexible polymeric matrix impregnated with a mixture of monocationic (1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (BMIm TFSI)) and a dicationic ionic liquid (1, 4-di(vinylimidazolium) butane bisbromide ([DVIM]Br)) facilitates rapid and extensive formation of electrical double layer when integrated with carbon-based electrodes. The resulting all-solid-sate flexible supercapacitor achieves superior scan rate operability (15, 000 mV/s) and ultralow relaxation time constant (7.8 ms), translating to high discharge current density (>1 mA/cm 2 ), energy density (26.4 Wh/kg) and power density (61, 127 W/kg). The improved rate capability (~83 %) and energy storage performance is attributed to a synergistic interplay of ionic strength, conductivity and ion mobility of the mixed ionic-liquid that unfold newer avenues towards solid-electrolyte engineering for energy storage devices. Highlights: Sluggish frequency response of solid-state supercapacitors is addressed. Ultrahigh scan rate operability (15 V/s) is achieved with mixed ionic liquid (IL) based solid-electrolytes. Synergistic interplay of ionic strength of the IL-mixture and ionic conductivity of the solid-electrolyte Strategy to extract the full capacitive potential of waste derived carbon electrodes.